FOREIGN DIRECT INVESTMENT UNDER UNCERTAINTY IN NIGERIA (2014)
Nigeria’s share of Foreign Direct Investment (FDI) inflows to Africa fell from 35.3% in 1990 to 13.6% in 2000 then rose to 16.3% in 2005 and stood at 14.1% in 2010. In theory, uncertainty adversely affects FDI inflows. However, very little attention is given to the effects of economic and political uncertainties on FDI inflows in developing countries. This study, therefore, examined the effects of economic and political uncertainties on FDI inflows to Nigeria at the aggregated and across sectors (agricultural, manufacturing, trade and business and mining and quarrying sectors), covering the period between 1970 and 2010. A traditional investment model, extended to incorporate the role of uncertainty on FDI inflows, was employed. An Error Correction Model (ECM) measuring the cost of capital, inflation and exchange rate variability, political instability and investors’ confidence was used to determine the short- and long-run effects of economic and political uncertainty on FDI inflows with data sourced from the Central Bank of Nigeria statistical Bulletin. The most preferred estimates were established using the Schwarz and Akaike information criteria. Prior to the estimations, stationarity conditions of each of the variables were ascertained using the Augmented Dickey Fuller (ADF) tests, while the Johansen method was used to determine cointegrating vectors. Tests of parameter stability, using the Chow test, were also carried out. Economic and political uncertainties adversely and significantly affected FDI at the aggregate level. Inflation, exchange rate variability, and cost of capital (real lending rate) had negative and significant (at P<0.05) effects on FDI inflows, both in the short-run (-0.16, -0.12, -0.38) and the long-run (-1.12, -0.12, -0.10). Economic and political uncertainties influenced FDI flows into the sectors only in the short-run in varying degrees. The cost of capital, exchange rate variability and inflation had significant and mostly negative impacts on FDI inflows into manufacturing (-0.08, -0.28, -0.15); mining and quarrying (-0.40, 0.23, -0.41); and trade and business services (-0.05, 0.05, -0.07) sectors. This implied that the FDI inflows to manufacturing, mining and quarrying, and trade and business services sectors were market-seeking cum efficiency-seeking, and economic uncertainty acted as a disincentive to the FDI inflows. The cost of capital and inflation had a negligible, but positive impact on FDI inflows to the agricultural sector (0.01, 0.01), while exchange rate variability was insignificant. This supported the view that the FDI inflow to this sector was resource-seeking. Economic and political uncertainties exerted a negative influence on Foreign Direct Investment inflows in the short- and long-run. The maintenance of a stable macroeconomic environment is essential if the adverse effects of economic uncertainty on Foreign Direct Investment inflows are to be effectively curtailed.